Contribution of bone marrow derived cells to the pancreatic tumor microenvironment - Scarlett, Christopher J. (Frontiers in Physiology, 2013)
Pancreatic cancer is a complex, aggressive, and heterogeneous malignancy driven by the multifaceted interactions within the tumor microenvironment. While it is known that the tumor microenvironment accommodates many cell types, each playing a key role in tumorigenesis, the major source of these stromal cells is not well-understood. This review examines the contribution of bone marrow-derived cells (BMDC) to pancreatic carcinogenesis, with respect to their role in constituting the tumor microenvironment. In particular, their role in supporting fibrosis, immunosuppression, and neovascularization will be discussed.